Anti-Aging in Caenorhabditis elegans of Polysaccharides from Polygonatum cyrtonema Hua - Zhang, Xue; Chen, Qi; Chen, Linzhen; Chen, Xiaolu; Ma, Zhiqiang (Molecules (Basel, Switzerland), 2024)
Polygonatum cyrtonema Hua, the dried rhizome of Polygonum multiflorum from the Liliaceae family, is a widely used medicinal herb with a long history of application. Its main active ingredients are polysaccharides, which have been demonstrated in contemporary studies to effectively delay the aging process. In the present study, homogeneous polysaccharide (PCP-1) was obtained after the purification and isolation of polysaccharides from Polygonatum cyrtonema Hua (PCP). The anti-aging activities of both were compared, and the possible mechanism of action for exerting anti-aging activity was explored using Caenorhabditis elegans (C. elegans). Research has indicated that PCP and PCP-1 exhibit potent anti-oxidant and anti-aging properties. Of particular note is that PCP-1 acts better than PCP. The two were able to prolong the lifespan of nematodes, improve the stress resistance of nematodes, reduce the accumulation of lipofuscin in the intestine, decrease the content of ROS and MDA in the body, increase the activity of the antioxidant enzymes SOD and CAT, promote the nuclear translocation of DAF-16, down-regulate the mRNA levels of the age-1 and daf-2 genes of the IIS pathway in nematodes, and up-regulate the expression of the daf-16, skn-1, sod-3, and hsp-16.2 genes. Based on the aforementioned findings, it is possible that the mechanism by which PCP and PCP-1 exert anti-aging effects may be through negative regulation of the IIS pathway, activation of the transcription factor DAF-16/FOXO, and enhancement of oxidative defenses and stress resistance in nematodes. Overall, the present study illustrated the great potential of polysaccharides from Polygonatum cyrtonema Hua in anti-aging and antioxidant activities. Specifically, PCP-1 demonstrated superior characteristics, which provides a reference for the future development of Polygonatum cyrtonema Hua polysaccharides.